2017
DOI: 10.21276/apjhs.2017.4.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health hazards among mortuary attendants at ndola teaching and arthur davison children’s hospitals

Abstract: Background: Just like employees from other occupations, Mortuary attendants are exposed to various hazards that may put their health at risk as they perform their duties. Objectives: The study was aimed at identifying occupational health hazards that mortuary attendants face at Ndola Teaching and Arthur Davison Children's Hospital mortuaries and to establish the infection control mechanisms in place. Methods: A descriptive crosssectional study was done among all (12) mortuary attendants at the two facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…Half (50%) of the present study participants were vaccinated against HBV when compared to no forensic mortuary staff being vaccinated against HBV in the Ndola study conducted in Zambia. 14 However, the percentage of forensic mortuary staff vaccinated against HBV in the present study is lower than that reported in a Chinese study where more than two thirds of staff were immunised. 19 These findings show variations in universal precautions being followed in different countries.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Half (50%) of the present study participants were vaccinated against HBV when compared to no forensic mortuary staff being vaccinated against HBV in the Ndola study conducted in Zambia. 14 However, the percentage of forensic mortuary staff vaccinated against HBV in the present study is lower than that reported in a Chinese study where more than two thirds of staff were immunised. 19 These findings show variations in universal precautions being followed in different countries.…”
Section: Discussioncontrasting
confidence: 86%
“…9 Many factors play a major role in compliance with using PPE, including PPE availability at the workplace. 14 The UK Royal College of Pathologists recommends using standard protective clothing for all forensic autopsies. 16 The present study revealed that not all workplaces always provided PPE and not all forensic mortuary personnel always used PPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Despite their crucial role in the healthcare system coupled with the many health hazards they are exposed to in their line of duty, mortuary workers in developing countries are often overlooked in studies on health and safety among health workers. 5,7 Also, people work for various incentives including financial rewards, which are necessary to increase productivity; 11 however, mortuary attendants in some developing countries are sometimes recruited and paid meagre salaries from internally generated funds of their facilities. 12 In Ghana, it has been noted that the lack of formal training and education makes it difficult if not impossible for mortuary attendants to seek career progression and promotion.…”
Section: Introductionmentioning
confidence: 99%